Metastatic conventional prostatic adenocarcinoma with diffuse chromogranin A and androgen receptor positivity. Issue 3 (27th February 2004) - Roudier, M P; True, L D; Vessella, R L; Higano, C S
Abstract : Conventional prostate adenocarcinomas consist mainly of tumour cells of luminal immunophenotype with scattered neuroendocrine (NE) cells. NE cells are defined by chromogranin A (CGA) immunoreactivity. Unlike luminal cells, NE cells lack androgen receptor (AR) and prostate specific antigen (PSA) immunoreactivity. This report describes the first case of conventional prostate adenocarcinoma expressing CGA, PSA, and AR as determined by immunohistochemistry. A 64 year old man was diagnosed with conventional prostate adenocarcinoma in 1993; he underwent cystoprostatectomy in 1994; he developed an iliac bone metastasis in 1997 and mediastinal lymph node metastases in 1999. All specimens obtained during the progression of the disease consisted primarily of luminal cells with only scattered NE cells. In contrast, in samples of non-osseous and osseous metastases obtained at necropsy in 2001, greater than 80% of tumour cells were shown to express PSA, AR, and CGA. This suggests that during tumour progression, conventional prostate adenocarcinomas may evolve into an NE cell phenotype.